BK Polyomavirus—Biology, Genomic Variation and Diagnosis - Jacek Furmaga; Marek Kowalczyk; Tomasz Zapolski; Olga Furmaga; Leszek Krakowski; Grzegorz Rudzki; Andrzej Jaroszyński; Andrzej Jakubczak (Viruses, 2021)
The BK polyomavirus (BKPyV), a representative of the family Polyomaviridae, is widespread in the human population. While the virus does not cause significant clinical symptoms in immunocompetent individuals, it is activated in cases of immune deficiency, both pharmacological and pathological. Infection with the BKPyV is of particular importance in recipients of kidney transplants or HSC transplantation, in which it can lead to the loss of the transplanted kidney or to haemorrhagic cystitis, respectively. Four main genotypes of the virus are distinguished on the basis of molecular differentiation. The most common genotype worldwide is genotype I, with a frequency of about 80%, followed by genotype IV (about 15%), while genotypes II and III are isolated only sporadically. The distribution of the molecular variants of the virus is associated with the region of origin. BKPyV subtype Ia is most common in Africa, Ib-1 in Southeast Asia, and Ib-2 in Europe, while Ic is the most common variant in Northeast Asia. The development of molecular methods has enabled significant improvement not only in BKPyV diagnostics, but in monitoring the effectiveness of treatment as well. Amplification of viral DNA from urine by PCR (Polymerase Chain Reaction) and qPCR Quantitative Polymerase Chain Reaction) is a non-invasive method that can be used to confirm the presence of the genetic material of the virus and to determine the viral load. Sequencing techniques together with bioinformatics tools and databases can be used to determine variants of the virus, analyse their circulation in populations, identify relationships between them, and investigate the directions of evolution of the virus.